Sustainable development factors for land development in UTM Johor Bahru campus [electronic resources] - 501114 Khalid Ahmed Mohamed; Fakulti Kejuruteraan Awam (2010)
Thesis (Sarjana Sains (Pengurusan Pembinaan)) - Universiti Teknologi Malaysia, 2010